Schema modes in criminal and violent behaviour of forensic cluster B PD patients: A retrospective and prospective study. (24th February 2014) - Keulen‐de Vos, Marije E.; Bernstein, David P.; Vanstipelen, Silke; de Vogel, Vivienne; Lucker, Tanja P. C.; Slaats, Mariët; Hartkoorn, Marloes; Arntz, Arnoud
Abstract : Purpose: A clear understanding of an offender's criminal behaviour is a prerequisite for determining suitable treatment. In the literature, several specific frameworks or therapeutic approaches that aim to explicate criminal behaviour can be distinguished (e.g., cognitive analytic therapy, offence paralleling behaviour paradigm), but Schema Therapy (ST) is becoming an increasingly popular paradigm. According to forensic ST's theoretical framework, criminal and violent behaviour can be explained by an unfolding sequence of schema modes, or moment‐to‐moment states that represent emotions, cognitions, and behaviour. In this study, we examine the validity of this theory and the relationship between schema modes, psychopathy, and institutional violence. Methods: Schema modes were assessed retrospectively from descriptions of patients' crimes in a sample of 95 hospitalized cluster B personality disordered offenders. Psychopathy was rated with the Psychopathy Checklist‐Revised and institutional transgressions were coded from daily hospital reports. Results: Our findings show that criminal behaviour is often preceded by schema modes that refer to feelings of vulnerability and abandonment, loneliness, and states of intoxication. Criminal behaviour itself is characterized by schema modes that refer to states of impulsivity, anger, and the use of overcompensatory strategies involving threats, intimidation, and aggression. Schema modes involving bullying and manipulation were positively correlated with the interpersonal facet of psychopathy; the vulnerable child mode was negatively correlated with the affective facet of psychopathy. The schema modes in this study moderately predicted later institutional transgressions. Conclusions: Our findings suggest that the schema mode concept is of explanatory value in understanding criminal and violent behaviour.